Study on Streptococcus agalactiae infection in Javanese medaka (Oryzias javanicus Bleeker, 1854) model - Amal, Mohammad Noor Azmal; Ismail, Ahmad; Saad, Mohd Zamri; Md Yasin, Ina Salwany; Nasruddin, Nurrul Shaqinah; Mastor, Siti Suhaiba; Abdul Rahman, Muhammad Hazim; Mohamad, Nurliyana (Elsevier, 2019)
This study determines the median lethal dose, and describes the clinico-pathological changes and disease development following Streptococcus agalactiae infection in Javanese medaka model. Javanese medakas were infected with S. agalactiae via intraperitoneal (IP) from 10⁴ to 108 CFU/mL, and immersion (IM) route from 10ᶟ to 10⁷ CFU/mL. The LD₅0–₂₄0h and clinico-pathological changes of the fish was determined until ₂₄0 h post infection (hpi). Next, the disease development was determined for 96 hpi in the fish following IP and IM infection at 10ᶟ CFU/mL and 10⁴ CFU/mL, respectively. The LD₅0–₂₄0h of S. agalactiae in Javanese medaka was lower following IP injection (4.5 × 102 CFU/mL), compared to IM route (3.5 × 10ᶟ CFU/mL). The clinical signs included separating from the schooling group, swimming at the surface of water column, lethargy, erratic swimming pattern, corneal opacity and exophthalmia. Histopathological examinations revealed generalized congestion in almost all internal organs, particularly in liver and brain, while the kidney displayed tubular necrosis. Both IP and IM routes showed significant positive correlation (p < 0.05) between the CFU/g of S. agalactiae in the fish tissue and fish deaths. Moreover, the lesions for histopathological scoring in selected organs following IP and IM challenges were also reflecting the CFU/g and fish deaths. This study indicates the capability of Javanese medaka as a model organism in study of streptococcosis development.